Brincar/jogo de papéis sociais e a educação infantil à luz da psicologia histórico-cultural - (:unkn) unknown (Universidade Federal de Goiás, 2018)
The present work consists in identifying and analysing it to play in the daily pay-school and in the documents norteadores of the childlike education of a local authority of the cultural-historical south-east from Goiás by the light of the theory. We look for the understanding of the existent relations in the context of the childlike education, our main objective identified and he analysed it to play in the municipal daily pay-school and in the documents norteadores for childlike education of the local authority of cultural-historical Catalão/GO by the light of the theory. As well as, to check how it takes place to discussion of playing and which place links occupies in the development / apprenticeship of the children in the daily pay-school in Catalão/GO, as well as to observe the paper attributed to him in the documents norteadores of the childlike education. The adopted theoretical referential system went to Psychology cultural-Historically. The theoretical distance of the study boards the general conception of childlike education in the quoted theoretical slope and together it does relations between development and educative practices in the pre-school age aiming to stand out to the paper of partners to play / play of papers. The methodology is ruled in the presuppositions of the dialectic-historical materialism, and it had like instrument metodológico, the observation participant and the documentary analysis, so the field work was carried out in municipal Catalan daily pay-school, and for documentary analysis we select the documents that orientate the childlike education. While analysing the data of the inquiry, elencando the categories of analysis, which they allowed to make us think to process of the cultural-Historical childlike development through the Theory. This trajectory allowed to detach two points that we find basic, being they: it to play / play of papers social is a historical construction and culture, and not something natural and spontaneous; and the official documents detach the importance of playing, however in a perspective construtivista, in other words, it treats the joke as a form naturalizante. As for the paper of the educator, we detach the relevance of the projection of the activities in the context of the childlike education, as soon as the activity only contributes to the childlike development when it is intentionally planned and mediated by the teacher with the purpose of enlarging the cultural repertoire of the child.
Play/social papers game and child education in the light of historical-cultural psychology
Keywords: Educação infantil; Brincar/jogo; Psicologia histórico-cultural; Childlike education; Toplay/play; Psychology cultural-historical; CIENCIAS HUMANAS::EDUCACAO